Evaluating energy consumption patterns in novel foamed ternary alkali-activated masonry blocks - Sunil Nandipati; Nikhil Kumar Degloorkar; Gandhi Pullagura; Debabrata Barik; Prabhu Paramasivam; Essam Althaqafi; Saiful Islam; Osamah J. Al-sareji (Scientific Reports)
Abstract This study endeavors to tackle the energy requirements of the building sector by employing passive design strategies. However, there exists a dearth of comprehension regarding the energy efficiency performance of foamed alkali-activated materials. To bridge this research gap, the study proposes a solution in the form of a thermally proficient wall material crafted from ceramic tile dust (CTD), class C fly ash (FA), and Ground Granulated Blast-Furnace Slag (GGBS), all of which are industrial by-products. The foamed ternary alkali-activated (FTAA) blocks, developed as a result of this research, exhibited commendable performance in terms of mechanical strength of 18.6 MPa, lower density of 1200 kg/m3, porosity of 15.95%, lower specific heat capacity (SHC) of 831 J/(Kg·K), and thermal conductivity (TC) of 0.38 W/(m·K). The thermal efficiency of FTAA blocks curtails the transfer of heat from the external environment to the interior, thereby engendering a more agreeable indoor milieu for occupants. A simulation study utilizing the eQuest tool was executed to evaluate the thermal attributes of the developed blocks and their consequential impact on energy requirements. The findings revealed that in comparison to clay bricks, employing FTAA blocks could yield potential annual energy savings of approximately 4%. Furthermore, notable cost savings of about 4.94% during peak summer months and 5.51% annually were observed. The significance of utilizing these ternary blocks, derived from industrial waste, resides in their affirmative contribution to environmental preservation, augmented indoor thermal comfort, and diminished energy consumption for end users. Consequently, this research makes a meaningful stride towards diminishing operational energy in buildings, harmonizing with sustainability objectives.